2014
DOI: 10.1097/hjh.0000000000000131
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fish oil improves endothelial function and lowers blood pressure via suppression of sphingolipid-mediated contractions in spontaneously hypertensive rats

Abstract: Objective Long-chain n-3 polyunsaturated fatty acids from oily fish reduce blood pressure (BP) in hypertension. Previously, we demonstrated that hypertension is associated with marked alterations in sphingolipid biology and elevated ceramide-induced vasoconstriction. Here we investigated in spontaneously hypertensive rats (SHRs) whether fish oil improves endothelial function including reduced vascular contraction induced via the sphingolipid cascade, resulting in reduced BP. Methods Twelve-week-old SHRs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 51 publications
2
19
0
2
Order By: Relevance
“…Interestingly, both BP reduction and LVH suppression were accompanied by favorable outcome in the present research. It was identified that SHR continued to develop further high BP level, which could also be seen in other studies on SHR model, leading to a higher incidence of LVH when compared with WKY rats 54 55 . Obvious formation of cardiac hypertrophy and over expression of EKR signaling pathway were identified in the C group.…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, both BP reduction and LVH suppression were accompanied by favorable outcome in the present research. It was identified that SHR continued to develop further high BP level, which could also be seen in other studies on SHR model, leading to a higher incidence of LVH when compared with WKY rats 54 55 . Obvious formation of cardiac hypertrophy and over expression of EKR signaling pathway were identified in the C group.…”
Section: Discussionsupporting
confidence: 72%
“…Four previous meta-analyses of clinical trials showed that fish oil or LC n -3 PUFA supplements can dose-dependently lower BP in hypertensive patients but not in normotensive individuals [ 6 , 7 , 8 , 9 ]. However, investigations using animal models have shown that diets enriched in n -3 PUFA can protect against induced BP elevations [ 10 , 11 ], and dietary deficiency of n -3 PUFA in young rats was associated with development of hypertension in later life [ 12 ]. Some observational studies have reported that an inverse association between fish or LC n -3 PUFA consumption and BP elevations in normotensive participants [ 13 , 14 , 15 ], while others found no association [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…By raising levels of adiponectin, n-3 PUFA indirectly cause additional NO expression. n-3 PUFA also protect the endothelium against angiotensin II-and glucose-mediated injury, lower membrane arachidonic acid content, and displace ceramide, thereby opposing ceramide signaling that induces vasoconstriction mediated by thromboxane [77]. Insertion of EPA into membranes interrupts waves of peroxidation, protects low-density lipoprotein cholesterol (LDL-C), and lowers the level of small, dense LDL-C (sdLDL), which itself causes endothelial dysfunction.…”
Section: Clinical Studies Of N-3 Pufamentioning
confidence: 99%